The Role Of Stress, Resilience, And Social Support In Academic Burnout Among Medical Students : A Systematic Review - Alya Chelsea; Arif Rachman; Agus Sutarman; Arfiyanti (Journal of Innovation Research and Knowledge, 2026)
Academic burnout has become an increasingly important mental health concern among medical students due to the demanding nature of medical education, characterized by intensive academic workloads, clinical responsibilities, and sustained psychological pressure. Understanding the psychological and environmental factors associated with academic burnout is essential for supporting students' well-being and academic success. This systematic review aimed to synthesize current evidence regarding the roles of academic stress, resilience, and social support in academic burnout among medical students. The review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines. Literature searches were performed in PubMed, Scopus, ProQuest, and Google Scholar. A total of 1,358 records were initially identified, of which 10 studies met the predefined eligibility criteria and were included in the final narrative synthesis following the PRISMA 2020 selection process. The synthesized evidence consistently identified academic stress as the principal psychological risk factor associated with academic burnout, whereas resilience and social support emerged as the primary protective factors associated with lower burnout levels. Additional determinants, including personality traits, academic adaptability, anxiety, workload, psychological well-being, and life satisfaction, were also associated with academic burnout, indicating that burnout is influenced by multiple interacting psychological, academic, and environmental factors. Overall, the findings highlight that academic burnout among medical students is a multifactorial phenomenon, highlighting the importance of integrated psychological and institutional strategies that address both psychological risk factors and protective resources to support students' well-being and foster healthier learning environments in medical education. However, the findings should be interpreted with caution because most included studies employed cross-sectional designs and substantial methodological heterogeneity precluded quantitative meta-analysis